2009
DOI: 10.1111/j.1742-4658.2009.07213.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microRNAs associated with hepatic stellate cell activation status identify signaling pathways

Abstract: Activation of hepatic stellate cells (HSCs), which is regulated by multiple signal transduction pathways, is the key event in liver fibrosis. Moreover, members of these pathways are important targets for microRNAs (miRNAs). To better understand the critical pathways of HSC activation, we performed comprehensive comparative bioinformatics analysis of microarrays of quiescent and activated HSCs. Changes in miRNAs associated with HSC activation status revealed that 13 pathways were upregulated and 22 pathways wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 32 publications
(33 reference statements)
3
82
0
Order By: Relevance
“…In our previous studies, we analyzed the miRNA expression profile in quiescent and in cultureactivated primary rat HSCs and identified 21 miRNAs [8]. Meanwhile, bioinformatic analysis revealed the signaling pathways regulated by these miRNAs in HSC activation, we found that apoptosis and cell-cycle pathways appeared to be the most enriched of these differentially downregulated signaling pathways [9].…”
Section: Introductionmentioning
confidence: 96%
“…In our previous studies, we analyzed the miRNA expression profile in quiescent and in cultureactivated primary rat HSCs and identified 21 miRNAs [8]. Meanwhile, bioinformatic analysis revealed the signaling pathways regulated by these miRNAs in HSC activation, we found that apoptosis and cell-cycle pathways appeared to be the most enriched of these differentially downregulated signaling pathways [9].…”
Section: Introductionmentioning
confidence: 96%
“…12,16,17 This comprehensive change in gene expression is associated with a pronounced dysregulation of miRNA synthesis. [18][19][20] Recent studies have shown that several miRNA, such as miR-16, 21 miR-27a/b, 20 miR-195, 22 and miR-335 23 are involved in proliferation or induced migration of myofibroblastic-activated HSC. Others such as miR-19b, miR-150, and miR-194 are suggested to participate in TGF-b signaling and myofibroblastic HSC activation, respectively.…”
mentioning
confidence: 99%
“…A number of reports have demonstrated that an important role is played by miRNAs during the activation of HSCs. The analysis of miRNA expression in activated rat HSCs identified a panel of up-regulated or down-regulated miRNAs (12). The overexpression of miR-16 and miR15b was also demonstrated to inhibit the proliferation of HSCs and to induce apoptosis through the down-regulation of the mitochondrial-associated anti-apoptotic protein Bcl-2, thereby leading to the activation of caspases 3, 8, and 9 (13).…”
mentioning
confidence: 99%